Conjugative DNA Transfer Is Enhanced by Plasmid R1 Partitioning Proteins - Gruber, Christian J.; Lang, Silvia; Rajendra, Vinod K. H.; Nuk, Monika; Raffl, Sandra; Schildbach, Joel F.; Zechner, Ellen L. (Frontiers in Molecular Biosciences, 2016)
Bacterial conjugation is a form of type IV secretion used to transport protein and DNA directly to recipient bacteria. The process is cell contact-dependent, yet the mechanisms enabling extracellular events to trigger plasmid transfer to begin inside the cell remain obscure. In this study of plasmid R1 we investigated the role of plasmid proteins in the initiation of gene transfer. We find that TraI, the central regulator of conjugative DNA processing, interacts physically and functionally with the plasmid partitioning proteins ParM and ParR. These interactions stimulate TraI catalyzed relaxation of plasmid DNA in vivo and in vitro and increase ParM ATPase activity. ParM also binds the coupling protein TraD and VirB4-like channel ATPase TraC. Together, these protein-protein interactions probably act to co-localize the transfer components intracellularly and promote assembly of the conjugation machinery. Importantly these data also indicate that the continued association of ParM and ParR at the conjugative pore is necessary for plasmid transfer to start efficiently. Moreover, the conjugative pilus and underlying secretion machinery assembled in the absence of Par proteins mediate poor biofilm formation and are completely dysfunctional for pilus specific R17 bacteriophage uptake. Thus, functional integration of Par components at the interface of relaxosome, coupling protein and channel ATPases appears important for an optimal conformation and effective activation of the transfer machinery. We conclude that low copy plasmid R1 has evolved an active segregation system that optimizes both its vertical and lateral modes of dissemination.